FLUXO DE POTÊNCIA ÓTIMO COM RESTRIÇÕES DA CURVA DE CAPABILIDADE DO GERADOR SÍNCRONO - Huatuco, Dionicio Zócimo ñaupari (2006)
This work presents the equations of operation limits of the synchronous machine that constitute the so called capability curve. From these mathematical equations, deduced from each one of these limits, the graphic of the operation curve is computationally generated, defining the operation region of the synchronous machine so that their windings do not itself deteriorate nor the machine loses stability in steady state. These equations are being included or implemented in the constraints of an optimal power flow (OPF). Actually these mentioned equations, neither have not been published on technical bibliography nor have these equations been used in OPF programs that consider the real operation limits of the synchronous machine. It is considered that the generation capacity of the active and reactive powers of a synchronous generator is limited by the complete capability curve, considering all its limits, and the principal target of this research work is the implementation of these limits in an OPF. The considered optimal power flow have been modeled as a nonlinear programming problem with an objective function that minimizes the total cost of generation of the active power, subject to a set of technical and economic constraints. The solution of the proposed OPF was obtained with the MATLAB® optimization functions. The proposed methodology has been successfully applied on the WSCC3 of 3 generator systems as well as on the New England 10 generators system, verifying that the operation costs are higher compared with the results of conventional OPF s programs that use capability curve approximated limits.